The Influence of Service Convenience and Promotional Strategies on Decisions to Transaction Using QRIS and Its Implications on Customer Loyalty - Dwi Setyo Aji; Zunan Setiawan; Dicky Jhon Anderson Butarbutar; M Huanza; Saida Zainurossalamia ZA (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to examine the impact of promotions and convenience of service on customer loyalty through the choice to transact using QRIS. This research is a quantitative investigation utilizing SPSS 26. The target population for this study consists of bank clients, with a sample size of 100. Data collection methods involve the use of a questionnaire. Based on the data analysis, it can be deduced that promotions and convenience of service have a noteworthy impact on transaction decisions using QRIS. Promotions and convenience of service significantly influence customer loyalty when utilizing QRIS. Transaction decisions do not significantly influence customer loyalty when using QRIS. Indirectly, promotions have a significant impact on customer loyalty through transaction decisions using QRIS. Indirectly, convenience of service has a significant impact on customer loyalty through transaction decisions using QRIS.